PENGARUH CARA PEMUPUKAN PUPUK CAIR NANOSILIKA MELALUI MEDIUM & PENYEMPROTAN PADA PERTUMBUHAN SUBKULTUR BIBIT ANGGREK - Dyah Ayu Kusuma Ningrum; Erma Prihastanti; Endah Dwi Hastuti; Agus Subagyo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
One way to increase supply orchid seedlings by subculture. Subculture of orchids often have hyperhidrisition. Hyperhidrisition can be overcome by unsure silica. This study aims to determine the effect of different ways through spraying fertilizer with the addition of fertilizer in the medium and analyze the results of the most effective influence on the growth of subculture of orchids. The study was conducted using a completely randomized design (CRD) with a single factor nanosilica fertilizer treatment in the medium and through spraying and each treatment was repeated three times. The treatment in this study are as follows: liquid fertilizer nanosilica M0K0 = 0% in the medium, liquid fertilizer nanosilica M0K1 = 75% in the medium, liquid fertilizer nanosilica M1K0 = 0% through spraying and liquid fertilizer nanosilica M1K1 = 75% by spraying. The data obtained were analyzed by ANOVA significance level of 95%. The results showed nanosilica fertilizer through spraying and the medium Vacint and Went (VW) increased the growth of subcultures Dendrobium sp. Liquid fertilizer application nanosilica with a concentration of 75% through the subculture medium most effectively promote the growth of plantlets subculture Dendrobium sp. Keywords: Dendrobium sp., subculture, fertilization, spraying, nanosilica